Functional MRI study of neurovascular coupling in patients with non-lesional epilepsy - Li, Zhisen; Hou, Xiaoxia; Lu, Yanli; Zhao, Huimin; Wang, Meixia; Gui, Qian; Wu, Guanhui; Xu, Qinrong; Dong, Xiaofeng; Cheng, Qingzhang; Xu, Xiaowen; Feng, Hongxuan (Frontiers in Human Neuroscience, 2025)
ObjectiveThe diagnosis of patients with non-lesional epilepsy (NLE) is relatively challenging because of the absence of a clear focus on imaging, and the underlying pathological mechanism remains unclear. The neuronal activity and functional connectivity of NLE patients are significantly abnormal, and the neuronal activity of epilepsy patients is closely related to cerebral blood flow (CBF). Neurovascular coupling (NVC) offers insights into the relationship between neuronal activity and CBF. Hence, we intend to explore the alterations of NVC in NLE patients and their influences on cognitive function.MethodsClinical data of 24 patients with NLE (15 female; age range 19–40 years; median age 30.5 years) and 39 healthy controls (27 female; age range 19–40 years; median age 30 years) were collected, and resting-state functional magnetic resonance imaging (rs-fMRI) and 3D arterial spin labeling (ASL) were performed. The imaging indexes of amplitude of low-frequency fluctuation (ALFF) and CBF were calculated, respectively, by post-processing analysis. The differences in CBF, ALFF and CBF/ALFF ratio between the two groups were analyzed, along with correlation with clinical data of NLE patients.ResultsCompared with the healthy controls, the CBF of the right parahippocampal gyrus was significantly decreased, and the CBF/ALFF ratio of the right inferior parietal, but supramarginal and angular gyri was significantly increased in NLE patients (p < 0.001). Moreover, the CBF/ALFF ratio was positively correlated with epilepsy depression score (r = 0.546, p = 0.006).ConclusionNLE patients showed abnormal local NVC, which was associated with the severity of depression. The combined application of rs-fMRI and ASL can comprehensively evaluate the neuronal activity and cerebral blood perfusion in patients with NLE. The abnormal NVC is of great significance for us to explore the central mechanism of the occurrence and development of NLE.